Pengaruh Tingkat Inflasi, Suku Bunga, Nilai Tukar, dan Produk Domestik Bruto Terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia Periode 2015-2024 - Miswanto, Tri; Octavia , Evi (Jurnal Pendidikan Indonesia, 2026)
Soil degradation is a major problem that threatens the resilience of agricultural production due to the reduced ability of the soil to support sustainable plant growth. This research aims to examine land degradation and its challenges to the resilience of agricultural production from the perspective of soil properties. The method used is a literature review with a narrative review approach to previous scientific research articles. The literature analyzed is publications from the last ten years that are relevant to soil degradation, soil physical and chemical properties, and agricultural productivity. The results of the study show that degradation of soil physical properties, such as compaction, structural damage, and erosion, as well as degradation of soil chemical properties, especially a decrease in organic matter and nutrient imbalance, have a significant effect on the decline and instability of agricultural production. The literature synthesis confirms that land degradation is a strategic challenge in maintaining the long-term resilience of agricultural production. Therefore, a land management approach based on soil quality is needed to support the sustainability of agricultural systems.